Correlation Between Total Mercury and Methyl Mercury-In Whole Blood of South Korean - Jung, Seon A; Chung, Dayoung; On, Jiwon; Moon, Myeong Hee; Lee, Jeongae; Pyo, Heesoo (Bulletin of the Korean Chemical Society, 2013)
In this study, total mercury and methyl mercury in whole blood of Korean was analyzed so as to investigate the correlation between total mercury (T-Hg) and methyl mercury (Me-Hg). 4000 whole blood samples were divided in four groups, according to T-Hg concentration in percentile: group I (p25-p50), group II (p50-p75), group III (p75-p95) and group IV (p95-p100). 100 samples were randomly selected from the each group, and Me-Hg concentration was measured. T-Hg concentration in whole blood was analyzed using a Direct Mercury Analyzer-80 and obtained limit of detection (LOD) was 0.2 μgL−1. Me-Hg concentration was analyzed with ethylate derivatization using headspace-gas chromatography-mass spectrometry, and obtained LOD of methyl mercury was 0.5 μgL−1. The geometric means of T-Hg and Me-Hg were 6.35 μgL−1 and 4.44 μgL−1, respectively, and 71.91% of T-Hg was presented as Me-Hg. KCI Citation Count: 9